2008
DOI: 10.1071/rd07164
|View full text |Cite
|
Sign up to set email alerts
|

Miniature ponies: 1. Follicular, luteal and endometrial dynamics during the oestrous cycle

Abstract: Follicular dynamics were studied during 12 interovulatory intervals (IOIs) and 36 preovulatory periods in Miniature mares. The percentage of IOIs with the following follicle events was: ovulatory wave with only one follicle>or=10 mm (55%), diameter deviation similar to previous reports in larger mares (25%) and minor waves emerging before or after the ovulatory wave (55%). Follicle data were compared among Miniature ponies, large ponies and Breton horses (n=12 IOIs per breed). The IOI was longer (P<0.001) in M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
4

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(13 citation statements)
references
References 23 publications
0
9
0
4
Order By: Relevance
“…Additionally, the mares were supplied with 1.0 kg of the concentrated feed (per day per animal) containing digestible energy of 2800 kcal/kg, 13.0 % of crude protein, and other ingredients (Equest Supra Animal Nutrition, São Leopoldo, Rio Grande do Sul, Brazil) as well as water and mineral salt (Suprasal Equino 80 Supra Animal Nutrition) ad libitum. LMs were monitored by ultrasonography to examine the follicles (ovaries), uterus, and cervix starting from the second postpartum day (two examinations in 2 days), until detection of follicles 30 mm in diameter (the sum of the larger and smaller diameter divided by 2) (Gastal et al 2008), when we started to examine the mares daily (Azevedo et al 2013). Finding of a follicle ≥ 35 mm in diameter with simultaneous edema of the endometrium (presence of endometrial folds), uterine tonus (Hayes and Ginther 1986), and the open cervix indicated the right time for intravenous injections of human chorionic gonadotropin (1500 IU HCG; Folligon, MSD, São Paulo, Brazil) to induce ovulation (Winter et al 2007).…”
Section: Horses and Methodsmentioning
confidence: 99%
“…Additionally, the mares were supplied with 1.0 kg of the concentrated feed (per day per animal) containing digestible energy of 2800 kcal/kg, 13.0 % of crude protein, and other ingredients (Equest Supra Animal Nutrition, São Leopoldo, Rio Grande do Sul, Brazil) as well as water and mineral salt (Suprasal Equino 80 Supra Animal Nutrition) ad libitum. LMs were monitored by ultrasonography to examine the follicles (ovaries), uterus, and cervix starting from the second postpartum day (two examinations in 2 days), until detection of follicles 30 mm in diameter (the sum of the larger and smaller diameter divided by 2) (Gastal et al 2008), when we started to examine the mares daily (Azevedo et al 2013). Finding of a follicle ≥ 35 mm in diameter with simultaneous edema of the endometrium (presence of endometrial folds), uterine tonus (Hayes and Ginther 1986), and the open cervix indicated the right time for intravenous injections of human chorionic gonadotropin (1500 IU HCG; Folligon, MSD, São Paulo, Brazil) to induce ovulation (Winter et al 2007).…”
Section: Horses and Methodsmentioning
confidence: 99%
“…All anestrous mares were assigned to GP4, and therefore GNP4 was composed of the remaining animals, which were in transitional phase. The follicles were measured based on the [(smaller diameter) + (larger diameter)] divided by 2 (Gastal et al 2008). Before the device was inserted, the vulva and perineum were cleaned with mild soap and water, and dried with a paper towel.…”
Section: Mare Selectionmentioning
confidence: 99%
“…Tiga ekor kuda mengovulasikan satu folikel dan satu ekor kuda mengovulasikan dua folikel dengan rataan diameter folikel dominan sehari sebelum ovulasi adalah 4,81±0,92 cm dan diameter korpus rubrum yang terbentuk adalah 3,82±0,45 cm (Gambar 1). Diameter folikel dominan tersebut tidak berbeda dibanding diameter kuda di daerah subtropis (Gastal et al, 2008). Hal ini membuktikan bahwa perubahan lingkungan subtropis ke daerah tropis tidak memengaruhi fertilitas kuda warmblood sebagaimana yang dikhawatirkan selama ini.…”
Section: Hasil Dan Pembahasanunclassified